Marijuana use development over the course of adolescence among North American Indigenous youth - Cheadle, Jacob E. (2012)
This study investigated the links between marijuana use trajectories and marijuana abuse/dependence (DSM-IV) using five waves of data from 718 North American Indigenous adolescents between 10 and 17 years from eight reservations sharing a common language and culture. Growth mixture models indicated that 15% of youth began using by 11–12 years of age and that another 20% began shortly thereafter. These early users had odds of abuse/dependence 6.5 times larger than abstainers. Girls were also unexpectedly found to be particularly at risk of early use, and this did not reflect other background and psychosocial factors, including friend use. While the timing, patterns, and consequences of use were similar to those reported for alcohol use previously, the social influences on use differed in important ways.